Kolonisasi Makrozoobentos pada Kolam Habitat Semi Ex Situ (HSE) di Kawasan Maninjau, Sumatera Barat (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2020)
Semi Ex-Situ Habitat (HSE) Pond is a pond that is designed for spawning native fish in Lake Maninjau, particularly in Bada fish (Rasbora argyrotaenia) in semi ex situ condition. This study aims to determine the benthic macroinvertebrates colonization in HSE ponds. The source of the water came from Lake Maninjau and the springs nearby. The study was conducted in August, October, and November 2018. Benthic macroinvertebrates samples were taken from some artificial substrate stainless steel- wire mesh (the size are 20 cm x 20 cm, mesh size 30), which was placed at the bottom of the ponds for 20â€”30 days. The result shows that there are five classes of benthic macroinvertebrates in an HSE pond with the water springs and HSE pond with the water of Lake Maninjau. Chironomidae was the most abundant Family in both the springs-HSE pond and the lake Maninjau-HSE pond. The abundance of benthic macroinvertebrates in these two ponds respectively, are 2207 individuals/m2 and 4138 individuals/m2. The Shanon-Wiener diversity index value is low, they are 0,38 in the springs-HSE pond and 0,29 in theÂ  lake Maninjau-HSE pond. The Bray Curtis similarity index values in those two HSE Ponds ranged from 47% to 63%, furthermore its categories from â€œnot similar to similarâ€.